Bartonella spp. in Fruit Bats and Blood-Feeding Ectoparasites in Madagascar - Brook, Cara E. (PLoS Negl Trop Dis, 2015)
We captured, ectoparasite-combed, and blood-sampled cave-roosting Madagascan fruit bats (Eidolon dupreanum) and tree-roosting Madagascan flying foxes (Pteropus rufus) in four single-species roosts within a sympatric geographic foraging range for these species in central Madagascar. We describe infection with novel Bartonella spp. in sampled Eidolon dupreanum and associated bat flies (Cyclopodia dubia), which nest close to or within major known Bartonella lineages; simultaneously, we report the absence of Bartonella spp. in Thaumapsylla sp. fleas collected from these same bats. This represents the first documented finding of Bartonella infection in these species of bat and bat fly, as well as a new geographic record for Thaumapsylla sp. We further relate the absence of both Bartonella spp. and ectoparasites in sympatrically sampled Pteropus rufus, thus suggestive of a potential role for bat flies in Bartonella spp. transmission. These findings shed light on transmission ecology of bat-borne Bartonella spp., recently demonstrated as a potentially zoonotic pathogen.